Competence, Regulation and Political Factors on Local Government Performance in Rembang Regency: The Role of Financial Report Quality as Mediation - Ika Rahmadiningsih; Marita Kusuma Wardani (Proceeding International Conference on Accounting and Finance, 2025)
The aim of this study is to identify the impact of competence, regulation, and political factors on performance through the quality of financial report. The approach used in this research is a quantitative method, collecting data through the use of questionnaires. The research object is the Regional Work Units (SKPD) of Rembang Regency. To test the hypotheses, the researcher employed Structural Equation Modeling (SEM) using Smart PLS version 3.0 software. The analysis includes external models, internal models, as well as hypothesis testing and mediation. The findings of the research show that competence, and regulation have a good influence on performance. But political factors, and financial report quality do not, it has an insignificant positive effect. Furthermore, rules and politics have a favorable impact on the quality of financial statements, but competence has an insignificant positive impact on the quality of financial statements. Furthermore, the quality of financial statement presentation has a positive but insignificant influence between talent, rules, and political factors in achieving performance results.